EVALUATION OF RISK FACTORS AFFECTING ANASTOMOTIC LEAKAGE AFTER REPAIR OF ESOPHAGEAL ATRESIA - ASKARPOUR, Shahnam (Arq Bras Cir Dig, 2015)
BACKGROUND: Anastomotic leak are reported among neonates who underwent esophageal atresia. AIM: To find risk factors of anastomotic leakage in patients underwent esophageal repair. METHODS: All cases with esophageal atresia were included. In this case control study, patients were classified in two groups according to presence or absence of anastomotic leaks. Duration of study was 10 years. RESULTS: Sixty-one cases were included. Mean±SD age at time of surgery in patients with leakage and without leakage was 9.50±7.25 and 8.83±6.93 respectively (p=.670). Blood transfusion and two layer anastomosis had significant correlation with anastomotic leakage. CONCLUSION: Blood transfusion and double layer anastomosis are associated with higher rate of anastomotic leakage.